Chain Rule - pp

# Chain Rule - pp - (8<<<Press any Key to...

This preview shows pages 1–3. Sign up to view the full content.

The Chain Rule The chain rule involves “taking the derivative normally” (often with the use of the power rule THEN taking the derivative of “what’s inside”). Consider a basi example…. f x ( 29 = 3 x 2 - 5 ( 29 3 Think of this like it ' s f ( x ) = z 3 and z = 3 x 2 - 5 f '( x ) = 3 z 2 d dx z So, use your basic power rule…. f ' x ( 29 = 3 x 2 - 5 ( 29 3 2 2 3 2 Now take the derivative of “what’s inside” and ‘tack that on the end’. f ' x ( 29 = 3 3 x 2 - 5 ( 29 2 6x <<<Press any Key to Continue>>> Simplifying give us the final result…. . f '( x ) = 18 x 3 x 2 - 5 ( 29 2

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Let’s do another example…. f x ( 29 = ln 8 x - 5 ( 29 Think of this like it ' s f ( x ) = ln( z ) and z = 8 x - 5 f '( x ) = 1 z d dx z So, take the derivative of the “log”…. f ' x ( 29 = 1 8 x - 5 ( 29 Now take the derivative of “what’s inside” and ‘tack that on the end’.
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: (8) <<<Press any Key to Continue>>> f ' x ( 29 = 1 8 x-5 ( 29 Simplifying give us the final result…. . f '( x ) = 8 8 x-5 Let’s do one final example…. f x ( 29 = e 3 x 4 Think of this like it ' s f ( x ) = e z and z = 3 x 4 ⇒ f '( x ) = e 3 x 4 d dx z f ' x ( 29 = e 3 x 4 Now take the derivative of “what’s inside” and ‘tack that on the end’. <<<Press any Key to Continue>>> First takethederivativeof the " e z " part f ' x ( 29 = e 3 x 4 12 x 3 ( 29 or f ' x ( 29 = 12 x 3 e 3 x 4...
View Full Document

## This note was uploaded on 06/15/2011 for the course MATH 122 taught by Professor Kustin during the Spring '08 term at South Carolina.

### Page1 / 3

Chain Rule - pp - (8<<<Press any Key to...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online